Inner disturbance: towards understanding the design of vertigo games through a novel balancing game - Byrne, Richard; Marshall, Joe; Mueller, Florian ‘Floyd’ (2016)
The design space of vertigo games is under-explored, despite vertigo underlying many unique body based game experiences, such as rock climbing and dancing. In this paper we articulate the design and evaluation of a novel vertigo experience, Inner Disturbance, which uses Galvanic Vestibular Stimulation to affect the player’s balance. Following study observations and a thematic analysis of Inner Disturbance (N=10), we present four themes and associated design sensitivities that can be used to aid designers of future digital vertigo games. With this work we aim to encourage others to experiment within this exciting new design space for digital games.